THE EFFECT OF FINANCIAL DECISIONS, EARNINGS MANAGEMENT AND INSTITUTIONAL OWNERSHIP ON THE VALUE OF BASIC MATERIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2020 - Kezia Citra Nathania; Hasnawati (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2023)
This study aims to determine the direct influence of funding decisions, earnings management, and institutional ownership on the value of companies in the basic material sector. This type of research is Quantitative, that is, the data is obtained from the financial statements for 2018-2020. The sampling technique uses purposive sampling therefore the company can be sampled as many as 61 companies with a total sample of 93 samples. The data obtained is then processed using SPSS software. The results showed that there is a positive relationship between funding decisions and institutional ownership to the value of the company, and a negative relationship between investment decisions and earnings management to the value of the company's basic material sector. Investment decisions and earnings management in the basic material sector of the company cannot be a determining variable for someone to invest.